Neonatal hand, foot, and mouth disease due to coxsackievirus A6 in Shanghai - Shanshan Xu; Huajun Li; Peng Qiao; Guofeng Xu; Dongying Zhao; Xiaoyan Lin; Yu Qin; Huiju Yu; Xi Zhang; Wanju Zhang; Lisu Huang (BMC, 2020)
Abstract Background Evidence of hand, foot, and mouth disease (HFMD) in neonates is limited. The aim of this study was to evaluate the clinical symptoms, pathogens, possible transmission routes, and prognosis of neonatal HFMD in Shanghai. Methods This was a case-control study based on the HFMD registry surveillance system. All neonates and infected family members were enrolled between 2016 and 2017 in Shanghai. Neonates with HFMD were followed for at least half a year. Detailed questionnaires, medical history, and physical examination were recorded. Routine blood examination, liver and renal function, immunophenotypes of peripheral blood lymphocytes (CD3, CD4, and CD8 T-cells; NK cells), immunoglobulin (Ig) M, IgG, and IgA, and cytokine interleukin (IL-1β, IL-2R, IL-6, IL-8, IL-10, and TNF-α) levels were measured. All rectal swab specimens were collected and genotyped for enterovirus, and phylogenetic analysis based on the VP1 sequences of coxsackievirus A6 (CV-A6) was performed to investigate molecular and evolutionary characteristics. T-test or nonparametric test was used to evaluate the differences. Logistic analysis was applied to calculate the risk of clinical manifestations in the group of HFMD neonates and their paired siblings. Results There were 16 neonates among the 12,608 diagnosed patients with HFMD, accounting for 0.13%. All neonatal infections were transmitted by other members of the family, mainly the elder siblings, and were caused by CV-A6. CV-A6 was the emerging and predominant causative agent of HFMD in Shanghai. None of the neonates with HFMD experienced fever, onychomadesis, or severe complications. However, two elder sibling patients showed lethargy, and one developed hypoperfusion. In the elder siblings with HFMD, the proportion of white blood cells was generally higher than in neonates with HFMD. The immunologic function of the neonates with HFMD was basically normal. The levels of inflammatory markers were higher in both neonates and elder siblings with HFMD compared to age-matched controls. The clinical symptoms receded about 1 week after onset. None of the neonates had sequelae. Conclusions In our study, CV-A6 infection in neonates was benign, but had the character of family clustering. Due to the two-child policy in China, elder siblings may be the main route of HFMD transmission.